Physical and figural animals in Patrick Deville's Peste & Choléra - Epp, Marla (My University, 2022)
This article studies the ways in which animals are represented as both “real” and “symbolic” fgures in Patrick Deville’s Peste & Choléra (2012). The novel focuses not only on the scientifc and medical developments in which its principal subject, the scientist Alexandre Yersin, was involved, but also presents the corresponding dark underside of this progress and the violence that accompanied the lifesaving and lifechanging innovations. Deville is known for exploring the complicated repercussions of historical events that continue to be felt to the present-day. I argue that throughout Peste & Choléra, scenes with animals serve as particularly sharp reminders that human advancement does not come without a cost. Although the animals appear primarily confned to scientifc laboratories or relegated to the edges of human settlements, Deville writes about them in an expansive style, constructing a complex web of layered biblical and literary references. I contend that, through these passages, Deville encourages a multiplicity of ways of reading animals and refuses to let them be carelessly cast as simply scientifc elements, forgotten victims of modernity.
Keywords: Patrick Deville; Peste & Choléra; Animals; Contemporary French literature; Science and technology